2016
DOI: 10.1017/s0952523816000067
|View full text |Cite
|
Sign up to set email alerts
|

Novel method using 3-dimensional segmentation in spectral domain-optical coherence tomography imaging in the chick reveals defocus-induced regional and time-sensitive asymmetries in the choroidal thickness

Abstract: Studies into the mechanisms underlying the active emmetropization process by which neonatal refractive errors are corrected, have described rapid, compensatory changes in the thickness of the choroidal layer in response to imposed optical defocus. While high frequency A-scan ultrasonography, as traditionally used to characterize such changes, offers good resolution of central (on-axis) changes, evidence of local retinal control mechanisms make it imperative that more peripheral, off-axis changes also be tracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…In addition, studies in chicks showed greater choroidal thickening in the central region than in the peripheral region in response to myopic defocus. 49 These findings indicate that the central retinal (including macular) regions are particularly responsive to visual stimulus conditions, leading to a decrease in choroidal vascularity and choriocapillaris blood perfusion during myopia development.…”
Section: Physiological Meaning Of the Choroidal Parameters In Ss-oct/mentioning
confidence: 72%
“…In addition, studies in chicks showed greater choroidal thickening in the central region than in the peripheral region in response to myopic defocus. 49 These findings indicate that the central retinal (including macular) regions are particularly responsive to visual stimulus conditions, leading to a decrease in choroidal vascularity and choriocapillaris blood perfusion during myopia development.…”
Section: Physiological Meaning Of the Choroidal Parameters In Ss-oct/mentioning
confidence: 72%
“…Chick retinas do not have a fovea, but have a largely rod-free area centralis that provides a visual acuity of approximately 7 cyc/deg 79–83. Optical coherence tomography (OCT) imaging shows that the retina is thickest in the region of the area centralis 84. The chick inner retina is avascular and is supplied with oxygen and nutrients by the pecten oculi, which is a vascular structure continuous with the choroid and projecting into the vitreous chamber.…”
Section: Animal Models Commonly Used In Studies Of Emmetropizationmentioning
confidence: 99%
“…To date, human studies have only examined foveal or nasal and temporal parafoveal choroidal thickness changes in response to full‐field defocus and suggest that the defocus mediated changes in choroidal thickness occur uniformly across the central macular area. However, studies in chicks have revealed that greater changes in choroidal thickness occur centrally, rather than peripherally, in response to full‐field optical defocus . Further, the altered ocular growth and refractive errors that are induced when form deprivation or optical defocus is imposed on only half of the retina (in both avian and mammalian animal models) are largely localised to the hemiretinal region exposed to image blur.…”
Section: Introductionmentioning
confidence: 99%
“…Research with animal models suggests that eye growth is influenced by retinal image defocus, with the choroid playing a significant role in mediating the effects of defocus on ocular growth and the development of refractive errors . Studies in a range of species show that a thinning or thickening of the choroid in response to hyperopic or myopic defocus results in a rapid movement of the retina towards the defocused image plane, followed by alterations in scleral growth that eventuates in the development of experimental myopia or hyperopia, respectively . In humans, short‐term exposure to full‐field myopic and hyperopic defocus in both children and adults has also elicited a transient increase or decrease in choroidal thickness respectively, implying that the choroid may contribute to the mechanisms involved in the longer‐term development of refractive errors in humans …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation